Amazonian Head Lice-Specific Genotypes Are Putatively Pre-Columbian - Boutellis, Amina (The American Society of Tropical Medicine and Hygiene, 2013)
Head and body lice are strict obligate human ectoparasites with three mitochondrial phylotypes (A, B, and C). Using molecular methods for genotyping lice (Cytochrome b and multi-spacer typing), and comparing our results with all the sequences of human lice that were genotyped previously, we assessed the presence of a specific American genotype that most likely predates the Columbian era in head lice collected from Amazonia.